2019
DOI: 10.1111/trf.15590
|View full text |Cite
|
Sign up to set email alerts
|

Platelet vesicles are potent inflammatory mediators in red blood cell products and washing reduces the inflammatory phenotype

Abstract: BACKGROUND: Studies suggest that washing red cell concentrates (RCCs) to remove soluble mediators and/or inflammatory components, such as extracellular vesicles (EVs), may lead to better clinical outcomes. This study tested the hypothesis that non-red blood cell (RBC) generated vesicles in RCC are potent inflammatory mediators in vitro and washing RCCs can reduce these vesicles and subsequently decrease the inflammatory activity of RCCs.From the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Irrespective of RBC shape recovery, however, patients may still benefit from the removal of harmful mediators contained in the RBC storage supernatant by washing. [42][43][44][45] Our study further showed that SE/S cells were the only morphologic class of RBCs that were irreversibly damaged by storage. Our previous work and current findings suggest that SE/S cells undergo lysis readily, even upon relatively minor perturbations such as medium exchange with isotonic or slightly hypotonic saline 17 and conventional centrifugation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Irrespective of RBC shape recovery, however, patients may still benefit from the removal of harmful mediators contained in the RBC storage supernatant by washing. [42][43][44][45] Our study further showed that SE/S cells were the only morphologic class of RBCs that were irreversibly damaged by storage. Our previous work and current findings suggest that SE/S cells undergo lysis readily, even upon relatively minor perturbations such as medium exchange with isotonic or slightly hypotonic saline 17 and conventional centrifugation.…”
Section: Discussionsupporting
confidence: 58%
“…If a similar level of shape recovery also occurs once stored RBCs are transfused into the body of the recipient, the resulting effect on blood rheology could potentially mitigate the negative effects of impaired RBC deformability typically associated with storage lesion. Irrespective of RBC shape recovery, however, patients may still benefit from the removal of harmful mediators contained in the RBC storage supernatant by washing 42–45 . Our study further showed that SE/S cells were the only morphologic class of RBCs that were irreversibly damaged by storage.…”
Section: Discussionmentioning
confidence: 58%
“…Of note, the number of CD235a + /AnV + microparticles in washed RBCs was higher than in standard RBCs following irradiation and storage. We have previously observed similar results, whereby the number of CD235a + /AnV + microparticles in washed RBCs was higher than in unwashed RBCs by day 14 post-wash. 21 While others have shown a reduction in red cell microparticles after washing, 22 this difference can readily be accounted for. Previous studies identified microparticles using only CD235a and size, 22 whereas we used size, CD235a, and annexin-V.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed similar results, whereby the number of CD235a + /AnV + microparticles in washed RBCs was higher than in unwashed RBCs by day 14 post-wash. 21 While others have shown a reduction in red cell microparticles after washing, 22 this difference can readily be accounted for. Previous studies identified microparticles using only CD235a and size, 22 whereas we used size, CD235a, and annexin-V. Furthermore, processing conditions such as the centrifugation speed, manual versus automated washing procedures, washing solutions, and post-wash storage solution influence microparticle generation.…”
Section: Discussionmentioning
confidence: 99%
“…The storage lesion is associated with oxidation of cellular structures, [6][7][8] depletion of key metabolites such as ATP and hemoglobin (Hb) regulator 2,3-diphosphoglycerate, 9 and microvesicle formation. 10,11 Microvesicle formation is thought to be a main cause of posttransfusion complications due to their role in: (a) the pathogenesis of thrombosis, 12 inflammation, [13][14][15] and responses to pathogens; 16 (b) platelet activation; 17 (c) deformability changes that affect RBC rheology and blood flow; 18 and (d) decreased oxygen delivery due to microvesicle-entrapped Hb, 19 among others. The extent of this storage lesion is highly variable depending on factors including, but not limited to, blood processing methods, [20][21][22][23][24] storage additive solutions, [25][26][27] and donorrelated characteristics.…”
mentioning
confidence: 99%